Public Debt Dynamics and Intra-Year Exchange Rate Fluctuations - Acosta Ormaechea, Santiago (IMF Working Papers; Working Paper, 2020)
The public sector, in carrying out its operations, often incurs foreign currency denominated liabilities and, as such, is exposed to exchange rate fluctuations that could affect the value of public debt to GDP ratios over time. This paper shows that converting foreign currency denominated flows and stocks into local currency using the average and the end-of-period exchange rates, respectively, as envisaged in public finance manuals, gives rise to an identifiable stock-flow adjustment term-due to intra-year exchange rate fluctuations-that affects public debt accumulation. Importantly, the inclusion of this often-ignored stock-flow adjustment term is critical to accurately project public debt levels and any related indicator that could in turn inform about the risk of debt distress. Using a novel dataset covering 82 countries during 2008-19, the paper shows that this stock flow adjustment term is sizable in countries experiencing large exchange rate depreciations, namely above the 99th percentile of the full sample, reaching 1.2 percent of GDP. Interestingly, the measurement of policy-related concepts such as interest rate-growth differentials and debt stabilizing primary balances are also affected by intra-year exchange rate fluctuations, and in non-negligible ways.